Recent development in electrolytic formation of carbon nanotubes in molten salts - Chen G.Z.; Fray D.J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
This article reviews the recent research development in the electrolytic production of carbon nano-tubes in molten salts. The experimental procedure and product morphologies of the electrolytic method are described in details. Different hypotheses of the carbon nano-tube formation mechanism in molten salts, particularly it relation with the erosion of the cathode, are compared and discussed. It is anticipated that the electrolytic method can potentially become a cheap and continuous process for the production of curved carbon nano-tubes, carbon sheathed metal nanowires and other carbon based nano-structures.